2020
DOI: 10.3390/microorganisms8081231
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Molecular and Serological Assessment of Hepatitis E Virus in Milk Samples

Abstract: Hepatitis E virus (HEV) infection is endemic in developing and developed countries. HEV was reported to be excreted in the milk of ruminants, raising the possibility of transmission of HEV infection through the ingestion of contaminated milk. Therefore, the detection of HEV markers in milk samples becomes pivotal. However, milk includes inhibitory components that affect HEV detection assays. Previously it was reported that dilution of milk matrix improves the performance of HEV molecular assay, however, the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…35,50 Recently we reported HEV-3 in the cow and goat milk in Assiut rural communities. 28,51,52 Interestingly, this patient (HEV-3 infected) was living in the same village where HEV-3 identified in the cow milk and the diagnosis was done within the same period. The patient reported that he often consumed unpasteurized cow milk and its products.…”
Section: Discussionmentioning
confidence: 99%
“…35,50 Recently we reported HEV-3 in the cow and goat milk in Assiut rural communities. 28,51,52 Interestingly, this patient (HEV-3 infected) was living in the same village where HEV-3 identified in the cow milk and the diagnosis was done within the same period. The patient reported that he often consumed unpasteurized cow milk and its products.…”
Section: Discussionmentioning
confidence: 99%
“…The HEV Ag assay might be helpful in screening new compounds due to its low cost and rapid performance compared with the molecular approaches. Interestingly, HEV ORF2 Ag was detected in cow and goat milk samples, indicating that this assay can be used for human safety studies as a food contamination marker 20,21,115 …”
Section: Future Perspectives For Hev Orf2 Protein As a Diagnostic Too...mentioning
confidence: 98%
“…Interestingly, HEV ORF2 Ag was detected in cow and goat milk samples, indicating that this assay can be used for human safety studies as a food contamination marker. 20,21,115…”
Section: Future Perspectives For Hev Orf2 Protein As a Diagnostic Too...mentioning
confidence: 99%
“…Hepatitis E virus (HEV) is the leading global cause of acute viral hepatitis. It infects approximately 20 million people annually, resulting in 70,000 deaths [10,11]. However, milk contains several substances, such as fats, casein, whey proteins, and lactose, that interfere with the extraction of viral nucleic acid and the recovery of enteric viruses [12].…”
Section: Hepatitis Virusesmentioning
confidence: 99%